Own experience of "Glicifon" using as a local chemotherapy drug for the patients with basal-cell head&neck carcinoma - D. N. Reshetov (Опухоли головы и шеи)
Introduction. Skin cancer is the most common type among the cancer statistics. It accounts up to 14.2 % of all types of cancer. Basal cell cancer (BCC) is the most common among the skin cancers. Despite the possibilities of using different types of treatment BCC the long-term results are infavorable-the relapse rates are still high and cosmetic results are unsufficient. Using the local chemotherapy is alternative method of head&neck BCC treatment.The study objective. Efficency analysis of using «Glycifon» as a local chemotherapy drug for head&neck BCC. Materials and methods. The study included 24 patients with head&neck BCC who underwent local chemotherapy with "Glycifon" drug. 18 (75 %) patients had primary tumors, 6 (25 %) - relapsed tumors. 7 (29.2 %) patients had multicentre BCC. All patients received local chemotherapy by "Glycifon" according to recommended instructions.Results. 79.2 % of patients had full regress of BCC after "Glycifon" local chemotherapy. Medium follow up time was 11.5 month. 2 patients (8.35) had to interrupt the treatment but for the intensive pain after the drug application. Other patients finished the therapy satisfactorily. No toxic reactions were observed. Inflammatory reactions in application zones were moderate and easily fixed. All patients who finished the therapy (100 %) we satisfied about the cosmetic results.Conclusion. Usage of "Glycifon" drug for local chemotherapy of head&neck DCC is effective, safe and cosmetic satisfied method. Possibility of using "Glycifon" in ambulatory treatment reduce the total medical & economic costs.